Burrow nests fall below critical temperatures of threatened seabirds but offer thermal refuge during extreme cold events - Cerren Richards; Sydney M. Collins; Kayla Fisher; Robert J. Blackmore; David A. Fifield; Amanda E. Bates (Canadian Science Publishing, 2024)
Climate change is altering the severity and intensity of extreme weather events. Occupying microhabitats that buffer extreme weather may help species avoid harsh environmental conditions. We describe the thermal microclimate of Atlantic Puffin (Fratercula arctica) and Leach's Storm-petrel (Hydrobates leucorhous) burrows and quantify whether burrows are thermal refuges during extreme cold weather events. We further test for the effect of weather conditions and burrow characteristics on nest microclimate and buffering capacity during extreme cold weather. We find that both species actively breed in burrow microclimates that are below their lower critical temperatures, which may impose significant thermoregulatory costs. However, burrows do act as thermal refuges because nests are kept 7.4-8.0 °C warmer than ambient temperatures during extreme cold weather events. Overall, external temperature and wind speed were strong drivers of burrow temperature, but burrow and habitat characteristics did not explain the variability in burrow buffering capacity during extreme cold weather. Our results suggest that burrows may provide a direct line of defence for seabird chicks against cold events. Given the complex responses of burrow microclimates to extreme events, quantifying how changes in environmental conditions will impact burrow-nesting seabirds in the future is key.